1997
DOI: 10.1002/(sici)1097-4636(19971205)37:3<314::aid-jbm2>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Effect of single-chain and two-chain high molecular weight kininogen on adsorption of fibrinogen from binary mixtures to glass and sulfonated polyurethane surfaces

Abstract: The adsorption of fibrinogen from a single protein solution and from binary mixtures of fibrinogen and high-molecular-weight kininogen (HK) to glass and four sulfonated polyurethane surfaces is reported. The effect of the single-chain (SCHK) and two-chain (TCHK) forms of HK on fibrinogen adsorption was investigated. Using radiolabeling methods, fibrinogen adsorption from a series of mixtures having the same weight ratio of fibrinogen to HK as in plasma (50:1), but varying in total concentration, was measured. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The outcome of the competitive behaviour onto the SCA surface has been previously observed using other proteins. Brash's group (Cornelius & Brash 1997) showed a significant reduction in fibrinogen adsorption on different surfaces when high-molecular-weight kininogen was co-adsorbed. In this study, results indicated that the presence of HSA had a negative effect on the level of adsorbed HFN.…”
Section: Protein Behaviour In Competitive Conditions: Binary Systemsmentioning
confidence: 99%
“…The outcome of the competitive behaviour onto the SCA surface has been previously observed using other proteins. Brash's group (Cornelius & Brash 1997) showed a significant reduction in fibrinogen adsorption on different surfaces when high-molecular-weight kininogen was co-adsorbed. In this study, results indicated that the presence of HSA had a negative effect on the level of adsorbed HFN.…”
Section: Protein Behaviour In Competitive Conditions: Binary Systemsmentioning
confidence: 99%
“…There are two possible explanations of this apparent discrepancy. First, the findings of Cornelius and Brash suggest that SC-HMWK undergoes a conformational transformation to DC-HMWK during the course of protein adsorption onto surfaces, 36 which also may have occurred under our culture conditions. Second, our SDS-PAGE results indicate the possible contamination of commercially obtained SC-HMWK by DC-HMWK (Fig.…”
Section: Discussionmentioning
confidence: 89%